Synthesis of Tungsten Trioxide/Hydroxyapatite (WO3/HAp) Photocatalyst For Methylene Blue Degradation - Khalid Mizar; Sri Mulyati; Nasrul Arahman (Elkawnie: Journal of Islamic Science and Technology, 2023)
Abstract: Dyes have toxic properties and complex chemical structures which become a threat to the ecosystem if it exposes to the environment. A photocatalyst is a semiconductor material that can run a photocatalytic process under UV or visible light to degrade most organic molecules, ideally to H2O and CO2. Tungsten trioxide (WO3) is a visible photocatalyst which could use sunlight irradiation to treat the wastewater pollutant. In this study, WO3 material was hybridized with hydroxyapatite (HAp) through the sol-gel method to degrade methylene blue (MB) synthetic pollutants. The FTIR and SEM-EDX characterization confirmed the presence element of the WO3/HAp hybrid material. The original WO3 and modified WO3/HAp photocatalysts with concentrations of 10, 15, and 20 mg were tested to degrade 15 ppm of 50 ml MB solution under visible light for 4 hours. The highest pollutant degradation was obtained using a 20 mg photocatalyst, which reached the photodegradation efficiency of 73.072% for WO3 and 88.689% for WO3/HAp. The result proved that WO3/HAp hybrid photocatalyst showed higher degradation performance than the unmodified WO3 photocatalyst. The results of this research can be developed for industrial wastewater treatment, including the papermaking, printing and dyeing industries.Abstrak: Zat warna  memiliki sifat beracun dan memiliki struktur kimia  kompleks yang dapat menjadi ancaman bagi ekosistem apabila terpapar ke lingkungan. Fotokatalis heterogen menggunakan semikonduktor yang memicu proses fotokatalitik dengan bantuan sinar UV atau sinar tampak dalam mendegradasi kebanyakan limbah organik, menjadi H2O dan CO2. Tungsten trioksida (WO3) merupakan fotokatalis yang dapat menggunakan cahaya matahari untuk mendegradasi polutan pada air limbah. Pada penelitian ini, WO3 dihibridisasi dengan hidroksiapatit (HAp) melalui metode sol-gel untuk mendegradasi polutan sintetik Methylene Blue (MB). Hasil karakterisasi FTIR dan SEM-EDX mengkonfirmasi unsur-unsur penyusun material  WO3/HAp. Fotokatalis WO3 munri  dan WO3/HAp yang dimodifikasi diuji untuk mendegradasi 15 ppm larutan MB 50 ml di bawah cahaya tampak selama 4 jam dengan konsentrasi 10, 15 dan 20 mg. Degradasi polutan tertinggi diperoleh dengan menggunakan fotokatalis 20 mg yang mencapai efisiensi 73,072% untuk WO3 dan 88,689% untuk WO3/HAp. Hasil tersebut membuktikan bahwa fotokatalis hybrid WO3/HAp menunjukkan kinerja degradasi yang lebih baik daripada fotokatalis WO3 tanpa modifikasi.